LITERATURE REVIEW: LOW SALT DIET IN PATIENT WITH HYPERTENSION - Nisrina Nur Zahidah (UNIVERSITAS AIRLANGGA, 2021)
ABSTRACTHypertension is still the most highest causes of death in Indonesia . Patient with hypertension not knowing that they have hypertension and in the end they have complications of hypertension, so it is often called the silent killer disease. Things that can be do so hypertension does not get worse is do a low salt diet. This study aims to determine the application of a low salt diet in patients with hypertension. The research method uses a traditional literature review, articles used by Portal Garuda and Google Scholar with a range of 2016-2020. The keywords used in the article search were low salt diet, hypertension. The results of the search for articles obtained on the Portal Garuda are 12 articles on Google Scholar are 4,030 articles, of which are only 15 articles that match the topic. Patients with hypertension mostly adhere to a low salt diet but there are still many who do not adhere to a low salt diet. Knowledge, attitude, family support and self awareness are factors that affects hypertension. The conclusion in this study, the application of a low-salt diet in hypertensive patients can be carried out well, hypertensive patients have knowledge, attitude and good family support for the implementation of a low salt diet and hypertensive patients who have the awareness to control their blood pressure. Suggestions for health workers can provide counseling regarding a low salt diet, for people with hypertension to apply a low salt diet properly so that blood pressure can be controlled.